Role of HSP-90 for increased nNOS-mediated vasodilation in mesenteric arteries in portal hypertension - Moleda, Lukas (Baishideng, 2010)
AIM: To explore the role of heat shock protein-90 (HSP-90) for nitrergic vasorelaxation in the splanchnic circulation in rats with and without portal hypertension. METHODS: Neuronal nitric oxide synthase (nNOS) and HSP-90 were analyzed by immunofluorescence, western blotting and co-immunoprecipitation in the mesenteric vasculature and isolated nerves of portal-vein-ligated (PVL) rats and sham operated rats. In vitro perfused de-endothelialized mesenteric arterial vasculature was preconstricted with norepinephrine (EC(80)) and tested for nNOS-mediated vasorelaxation by periarterial nerve stimulation (PNS, 2-12 Hz, 45V) before and after incubation with geldanamycin (specific inhibitor of HSP-90 signalling, 3 μg/mL) or L-NAME (non-specific NOS-blocker, 10(-4) mol/L). RESULTS: nNOS and HSP-90 expression was significantly increased in mesenteric nerves from PVL as compared to sham rats. Moreover, nNOS and HSP-90 were visualized in mesenteric nerves by immunofluorescence and immunoprecipitation of nNOS co-immunoprecitated HSP-90 in sham and PVL rats. PNS induced a frequency-dependent vasorelaxation which was more pronounced in PVL as compared to sham rats. L-NAME and geldanamycin markedly reduced nNOS-mediated vasorelaxation abrogating differences between the study groups. The effect of L-NAME and geldanamycin on nNOS-mediated vasorelaxation was significantly greater in PVL than in sham animals. However, no difference in magnitude of effect between L-NAME and geldanamycin was noted. CONCLUSION: HSP-90 acts as a signalling mediator of nNOS-dependent nerve mediated vascular responses in mesenteric arteries, and the increased nitrergic vasorelaxation observed in portal hypertension is mediated largely by HSP-90.